A Challenging Case of Atypical Papillary Proliferation of Nipple with Loss of Myoepithelial Layer Cells; a Diagnostic Dilemma. (9th November 2022) - Pettit, K; Rahmanov, N; Hassan, M
Abstract: Introduction/Objective: Papillary breast lesions are comprised of a broad spectrum of entities ranging from benign conditions like intraductal papilloma to invasive carcinoma. These lesions account for less than 3% percent of breast tumors and less than 2% of breast malignancies. The wide range and overlap in the clinical, imaging, and histologic characteristics of these lesions can often make them difficult to classify. Here we present a case of a challenging neoplastic nipple papillary lesion with a differential diagnosis ranging from nipple adenoma with atypia to papillary carcinoma. Methods/Case Report: 48-year-old female with history of left nipple mass for 6 months, presented to the emergency department with mild bleeding from the left nipple for two hours. Breast ultrasound showed a group of fine pleomorphic calcifications within a mass arising from the left nipple, highly concerning for Paget's disease. Histopathology revealed papillary proliferation of well-formed round structures within a variably fibrous/hemorrhagic stroma. The nodules exhibited papillary fronds with epithelial hyperplasia of monotonous low-grade cells, and scattered mitoses, forming relatively rigid/luminal structures with polarization. No desmoplasia or conventional infiltrative pattern was seen. Immunohistochemical staining showed strong expression for estrogen receptor (ER). Cytokeratin 5/6, p63 and calponin did not highlight the myoepithelial layer in the papillary elements or around the round structures. A diagnosis of atypical papillary proliferation was rendered to warrant an excision. Subsequently, the patient underwent total mastectomy, which revealed conventional invasive ductal carcinoma with lymphovascular space invasion. Results (if a Case Study enter NA): NA Conclusion: Atypical papillary lesions of the nipple are difficult to classify in a limited biopsy material. The loss of myoepithelial cell layer makes interpretation even more challenging. Extreme caution should be taken in assigning neoplastic nature to the lesions in biopsy which eventually guide the surgeon in making decision to preserve the nipple or not.